"Not what I thought!" information seeking behaviors of international students during the application for graduate study in the USA. Issue 1 (24th October 2017) - Huang, Li‐Min; Bilal, Dania
ABSTRACT: A recent study revealed that international students' reading comprehension scores on the Test of English as a Foreign Language (TOEFL) equates to 12 th ‐grade reading comprehension level (Taylor, 2017 ). In evaluating the admission materials at selected flagship universities in the United States, Taylor (2017) found that the reading comprehension level ranges from 15 th ‐grade to 19 th ‐grade level. The readability of these materials can be challenging to international graduate students. Though a large body of literature exists about international graduate students in the United States, scant work has explored international doctoral students' information seeking behaviors and experiences while applying for doctoral study. We report the results of a study that explored the behaviors and experiences of 14 international doctoral students studying at a flagship university in the United States. Using in‐depth interviews, we found that the students used two types of resources, experiential (EXR) and authorized (AUR), and began looking for information by exploring the former. We identified three common themes of their information seeking behaviors and problems they experienced in using official websites. The findings have implications for improving the design of websites to support international students' information seeking and needs.